Simultaneous cooling the coupled nano-mechanical resonators in the strong optomechanical coupling regime. (11th April 2019) - Wang, Qiong; Xu, Lan; Wang, Ya-Min
Abstract: Coupled nano-mechanical resonators (NRs) have recently attracted great attention for both practical applications and fundamental studies. As a preparation step, it is needed to cool the coupled NRs to their ground states. In this paper, we investigate the coupled mechanical resonators cooling by employing the covariance approach for the identical and nonidentical cases, special attention is paid to the strong optomechanical coupling regime. Using numerical investigations, we show that the two coupled NRs can be simultaneously cooled down to nearly the vibrational ground state with the strong optomechanical coupling with the RWA. For these reasons, our scheme may provide a new paradigm for the coherent manipulation of NRs in the strong optomechanical coupling regime.